Computer(ized) linguistic resources at the L. Štúr Institute of Linguistics - Garabík, R. (Лексикографічний бюлетень, 2006)
Abstract. Ľ. Štúr Institute of Linguistics, as the main linguistic institution in the Slovak
Republic, publishes a lot of information either in the form of dictionaries, scientific publications or periodicals, targeted both to scientific community and general audience. With increasing amount of information produced, information retrieval and effective searching can be greatly assisted by organizing and indexing electronic versions of the documents. As a public service, the Institute offers some of the data to be accessed and searched on the Internet.